Adaptation of the Russian enterprises activities to sanctions restrictions - E. A. Panova (Вестник университета)
Anti-Russian sanctions represent a large-scale range of restrictions imposed by the coalition of countries. They include blocking financial, investment, import, and export operations with Russia. The sanctions have affected almost all economic entities, even those not directly dependent on foreign markets. The purpose of the study is to identify main areas of the sanctions impact on Russian enterprises in combination with a set of adaptation measures to the restrictions imposed. The study is based on the methods of comparative analysis, generalization, and systematization. The article considers difficulties faced by enterprises after the sanctions introduction and ways of building new business relationships with counterparties from “friendly” countries. The results obtained can be useful for enterprises of various activity spheres when solving issues of increasing commodity flows and improving economic results under the current conditions.